2008
DOI: 10.1007/s00268-008-9477-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of Recurrence of Multinodular Goiter: An Evidence‐based Review of the Literature

Abstract: The definitive management and prevention of recurrence of benign nodular goiter is primarily surgical. Total thyroidectomy essentially eliminates the risk of recurrence without an accompanying increased risk of permanent hypoparathyroidism or RLN injury. Therefore, total thyroidectomy should be considered the procedure of choice for benign multinodular goiter whenever possible, especially considering that reoperations for goiter are significantly more morbid than any initial operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 96 publications
5
121
1
7
Order By: Relevance
“…Another feared complication of repeated thyroid surgery is permanent hypoparathyroidism which can be a very disabling complication (18) . A very high risk of hypoparathyroidism was noticed in literature for reoperative thyroid surgery: it has been reported that the incidence of transient hypoparathyroidism was 0% to 25% and of definitive hypoparathyroidism from 0% to 22% (7,8,18,20,21) . The exact position of parathyroid glandsmay be obscured by scar tissue from the previous operative procedure (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another feared complication of repeated thyroid surgery is permanent hypoparathyroidism which can be a very disabling complication (18) . A very high risk of hypoparathyroidism was noticed in literature for reoperative thyroid surgery: it has been reported that the incidence of transient hypoparathyroidism was 0% to 25% and of definitive hypoparathyroidism from 0% to 22% (7,8,18,20,21) . The exact position of parathyroid glandsmay be obscured by scar tissue from the previous operative procedure (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Risk of recurrent goiter after subtotal thyroidectomy, which ranges from 3% to 43 % (1)(2)(3) . Suppression of TSH L-thyroxin therapy can be used to prevent the recurrence and is useful only in 30 % of patients (1,(4)(5)(6)(7)(8)(9) . Reoperative thyroid surgery is indicated in case of recurrent unilateral or multi nodular goiter, when it is associated with compression or in case of suspected malignancy, and in recurrent thyrotoxicosis (7,10) .…”
Section: Introductionmentioning
confidence: 99%
“…In thyroid malignancies several activated oncogenes have been found [27]. There are also other factors like positive family history, young age at presentation, bilateral disease and multinodular vs. single nodules which have been accepted risk factors for goiter recurrence [28]. We should not forget about the environmental chemicals and drugs which are goitrogenic in humans e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is an important treatment option in the presence of indications (compressive symptoms, high suspicion of malignancy, hyperthyroidism, cosmetic preference, etc.) [2]. There are several alternative procedures for thyroid gland operation such as subtotal thyroidectomy (STT), neartotal thyroidectomy (NTT), hemi-thyroidectomy plus subtotal resection (Dunhill procedure), and total thyroidectomy (TT).…”
Section: Introductionmentioning
confidence: 99%
“…There are several alternative procedures for thyroid gland operation such as subtotal thyroidectomy (STT), neartotal thyroidectomy (NTT), hemi-thyroidectomy plus subtotal resection (Dunhill procedure), and total thyroidectomy (TT). But the surgical procedure of choice is still under discussion [1][2][3]. There are some studies which prefer TT method because of the lower incidence of goiter recurrence and less frequent need for completion thyroidectomy, especially when there is a bilateral gland involvement posterior to middle thyroid veins [4,5].…”
Section: Introductionmentioning
confidence: 99%